Assessing acute nicotine impact on choroidal thickness: a randomized, double-blinded study comparing smoking cessation aids, including nicotine gum and electronic cigarettes - Alhazmi, Mohammed; Alotaibi, Wafa; Almansour, Saud; Alotaibi, Sadeem; Alanazi, Muteb; Althomali, Mohammed (International ophthalmology, 2024)
Purpose To explore whether differences in choroidal thickness arise from nicotine consumption in healthy young individuals, specifically comparing the effects of nicotine gum to electronic cigarette (vaping), while maintaining a consistent 4 mg nicotine dosage. Methods In a randomized double-blinded prospective cross-sectional study, 20 healthy participants (mean age ± standard deviation: 23 ± 2.36 years) were randomly assigned to either the nicotine gum or vaping group. Choroidal thickness (ChT) measurements were conducted using optical coherence tomography (OCT) (Topcon 3D OCT-1 Maestro System) at baseline, 30, and 60 min after ingesting 4 mg of nicotine, with ChT measurements taken from five different horizontal areas. Results Neither the nicotine delivery method (gum or vaping) demonstrated a statistically significant impact on ChT mean scores among subjects in the five measured areas at baseline, 30, and 60 min ( p > 0.05). However, significant differences were observed in ChT mean scores within subjects across the five areas (F (1.83, 72) = 36.43, p < 0.001), regardless of other study factors such as group, time, and visit ( p > 0.05). A statistically significant interaction was identified between the factors of area and time concerning participants' ChT mean scores when stratified by the type of smoking (tobacco, vaping, and dual) ( p = 0.003). Conclusion The results of this study revealed that nicotine, up to particular concentration of 4 mg, does not have a statistically significant vasoconstrictive effect on choroidal thickness, regardless of the delivery method, within the examined group. These findings offer valuable insights into the relationship between nicotine intake and choroidal dynamics in young adults.